O crescimento desordenado das cidades sobre áreas de proteção ambiental: o princípio da boa-fé e a proteção ao direito de moradia - Reis, João Emílio de Assis (2015)
This study analyzes the conflict between the fundamental right to housing and the fundamental right to the environment, in the case of illegal occupation of Environmental Protection Areas under the principle of good faith applied in relations between the state and citizens. The intense urban growth occurred in the world from the twentieth century has provoked numerous socioeconomic and territorial changes in the country and huge problems. The expansion of cities, especially in developing countries like Brazil is even worse, given the fact that combine intensive urbanization, environmental degradation, with a historical formation characterized by economic inequality and inefficiency of the government. One of the effects of urban growth at this juncture is the housing deficit that forces people to seek alternatives for housing, which too often end up breaking the law, degrade the environment, and often endanger their own lives. In this context, it is common to invasion or irregular land subdivision in environmentally protected areas, which are of limited use, such as Permanent Preservation Areas, which creates a relevant social problem to be solved. It analyzes first the formation of the housing problem scenario, considering the historical formation of Brazilian cities, the urban property and public housing policy. The following is based on an analysis of the evolution of the incorporation of the housing and protection of the environment to the law as rights, analyzes the presence of both as fundamental rights in the Constitution of 1988, seeks to present the principle of good faith, as a constitutional rule of law reputable protect occupants populations of Protected Areas in consolidated situation, due to the confidence of the protection of the need - here meaning legal certainty and predictability in the government's performance - in state relations versus citizens. Studies the principle of good faith from its core in private law, analyzing its development and evolution in the Brazilian public law, to then apply it specifically in the case of irregularly occupied Permanent Preservation Areas, trying to analyze both the possibility of removal of these populations as the regularization of these occupations, based on the technique of balance between fundamental rights